Sufi-Empower: Psychological First Aid to Prevent Mental Health Deterioration in Sandwich Generation Students - Alviani, Mitha; Tajul C, M. Aryachi; Rosidah, Jamila (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The "Sandwich Generation" phenomenon in Indonesia has become a significant issue due to rapid population growth. This generation, the majority of whom are 20-29 years old, face a double burden of family and professional responsibilities which have the potential to trigger stress and burnout. This condition has a huge impact on students who also work, resulting in physical and mental fatigue and degradation of mental health. To overcome this problem, a solution is needed in the form of Psychological First Aid (PFA) which is equipped with a religious approach. The "Sufi-Empower" program is proposed as a form of PFA based on Islamic psychotherapy, using Sufistic techniques to strengthen mental health through activities such as muhasabah, qiro'atil qur'an, and mujahadah. This program aims to provide sustainable mental support, reduce stress, and increase the meaning of life for sandwich generation students. The implementation involves universities, with the main activity "Rihlah Camp" which integrates the PFA approach with Islamic values. Through this program, it is hoped that sandwich generation students can live more optimistic and productive lives, and avoid the risk of mental health degradation.